Risk preference and child labour: Econometric evidence - Raymond Boadi Frempong; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2020)
The literature suggests that the household invests in the human capital of a child member not only for altruistic reasons but also as insurance against future income shocks. Hence, the allocation of the child's time between school and work is a function of the risk preference of the household head. This paper estimates the effect of parental risk preference on child labour decisions in the household using recall information on child labour and a risk elicitation question. We address endogeneity issues by applying an instrumental variable estimation technique. We find that risk-averse households are more likely to send their children to work. Further analyses suggest that such outcomes are driven by the need to maximise the household's expected income from the child. Evidence from instrumental variable regressions indicates that the relationship between risk aversion and child labour is causal and that risk aversion induces higher probabilities of children working.
Keywords: D13; D15; D64; 330; altruism; child labour; household welfare; human capital; risk preference; uncertainties